Numerically evaluate axial force variations of jointed precast piles during construction - Md. Foisal Haque; Ishtiaque Ahmed (Discover Geoscience)
Abstract The axial force variation along the length of the jointed precast pile is influenced by the hard soil layer properties during construction. For this purpose, this research proposes an innovative concept of spring model of jointed precast pile to evaluate the axial force variations along the length to consider some variable parameters (i.e. soil elastic moduli, soil Poisson’s ratios, hammer loads, compressive strengths and sizes of precast piles). The linear elastic analysis is performed by using finite element-based software ETABS v. 18.1.1 to consider 3-nodded line element of the jointed precast pile. Variable parameters are influenced to increase the normalized axial force of the jointed precast pile because of increasing stiffness, self-weight, etc. The difference in result of 6.84% may indicate a good agreement with the verification of the numerical analysis. The rates of the normalized axial force increments for variable soil elastic moduli, soil Poisson’s ratios, and precast pile sizes are found to be (1 to 2) %, (1.25 to 1.75) %, and (27 to 36) %, respectively. In addition, the maximum axial force increment rate is found to be 0.47% for precast pile sizes of 400 × 400 and 450 × 450 mm.